Left Hand Dominance Affects Supra-Second Time Processing - Vicario, Carmelo M.; Bonnì, Sonia; Koch, Giacomo (Frontiers in Integrative Neuroscience, 2011)
Previous studies exploring specific brain functions of left- and right-handed subjects have shown variances in spatial and motor abilities that might be explained according to consistent structural and functional differences. Given the role of both spatial and motor information in the processing of temporal intervals, we designed a study aimed at investigating timing abilities in left-handed subjects. To this purpose both left- and right-handed subjects were asked to perform a time reproduction of sub-second vs. supra-second time intervals with their left and right hand. Our results show that during processing of the supra-second intervals left-handed participants sub-estimated the duration of the intervals, independently of the hand used to perform the task, while no differences were reported for the sub-second intervals. These results are discussed on the basis of recent findings on supra-second motor timing, as well as emerging evidence that suggests a linear representation of time with a left-to-right displacement.